2021
DOI: 10.26668/businessreview/2022.v7i1.279
|View full text |Cite
|
Sign up to set email alerts
|

Life interrupted, but performance improved: Rethinking the influence of technology-mediated interruptions at work and personal life

Abstract: Purpose: This paper aims to analyze the effects of the technology-mediated interruptions on the conflicts and the performance of individuals during their work and non-work time. Theoretical framework: This work is based on the Conservation of Resources Theory, focusing on conflict and quality of life in the digital age. Design/methodology/approach: To evaluate the influence of technology interruptions on conflicts and performance, we applied a survey to management and accounting professionals and obtained 399 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…According to Chen and Karahanna (2014) and Maçada et al (2022), technology is linked to feelings of dissatisfaction at the workplace, stressful work life, and psychological burnout. Also, one negative outcome of technology is commonly seen among employees when they make excessive use of technology for professional activities even during their personal time (Hubbard, 2016).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Chen and Karahanna (2014) and Maçada et al (2022), technology is linked to feelings of dissatisfaction at the workplace, stressful work life, and psychological burnout. Also, one negative outcome of technology is commonly seen among employees when they make excessive use of technology for professional activities even during their personal time (Hubbard, 2016).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Also, one negative outcome of technology is commonly seen among employees when they make excessive use of technology for professional activities even during their personal time (Hubbard, 2016). Another adverse effect includes frequent usage of technology for entertainment purposes, even during work hours (Maçada et al, 2022). Hubbard (2016) points out that, on average, an American spends around three hours every day utilizing electronic gadgets and browsing the internet.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Path analysis interpreted the results of this study. Maçada et al (2021) imply four analysis patterns, including an instrument test (reliability and validity), a normality test, a model test, and a hypothesis test (partial).…”
Section: Model Specificationmentioning
confidence: 99%
“…Antonio Carlos Gastaud Maçada et al (2022) in their study observed that technologymediated interruptions affect work-family conflict.…”
Section: Introductionmentioning
confidence: 99%